Under which conditions is carrier cooperation possible? A case study in a Seville marketplace - Muñuzuri, Jesús; Escudero-Santana, Alejandro; Aparicio-Ruiz, Pablo (Transport, 2018)
The high volume of traffic originates two well-known problems in many cities: congestion and pollution. In recent years, a social phenomenon is emerging cooperation. This work is aimed at evaluating the circumstances under which transport cooperation is possible between different stakeholders operating in the same geographical area. To this end, a double survey process was conducted in a marketplace situated in the Seville City (Spain) centre. The first survey was designed to know the characteristics of the retailers and their preferences with respect to cooperation and regulations. A relational analysis between retailer features and their willingness to cooperate was carried out. After analysing the motivations for non-cooperation, a mixed proposal was designed and surveyed. Although the research was limited to a marketplace, the relevant data gathered from this double survey process highlights some implications: (a) the importance of personal relations in retailer cooperation; (b) a high volume of freight and the use of vans as on-street warehouses appear as significant motivations for non-cooperation; (c) forcing changes in the statu quo encourages cooperation.